Study of the relative bioavailability of a multisource formulation of sulfamethoxazole regarding the drug reference - Alvarado Yarasca, Ángel (2016)
Objective: To determine the relative bioavailability of an oral formulation of multisource sulfamethoxazole 200 mg / 5 ml respect to the reference formulation Oryctolagus cuniculus L (albino rabbits). Material and methods: The samples studied consisted of 25 vials of suspension of sulfamethoxazole / trimethoprim multisource 200 mg: 40 mg / 5 ml T1 with the letter assigned to the batch 11070674; and as a reference (R) 25 flasks Bactrim suspension of 200 mg: 40 mg / 5 ml, RJ0774 batch. The protocol consisted of a single oral dose of 100 mg / kg of sulfamethoxazole 200 mg / 5 ml of each of the formulations to 12 albino rabbits after a 12 hour fasting, through an open design in two cross periods (T / R), randomized, double-blind study with a greater range of 5 half-lives between each administration, later to determine plasma concentrations of the drug in default until 12 hours by means of a spectrophotometric method periods of time colorimetric diazotization. With the data of plasma, bioavailability curves were constructed, including the area under the curve (ABCo-12h , ABCo-∞ ), Cmax and tmax were determined. Results: According to statistical analysis for bioequivalence, it was found: ABCo-12h T1 / ABCo-12h R CI 90% from 0.873 to 1.021, AUCo-∞ T1 / AUCo-∞ R 90% CI 0.868 to 1.032 and Cmax T1 / Cmax R CI 90% 0,866- 1,045. Conclusions: The values of multisource sulfamethoxazole found are within the acceptable range of bioequivalence proposed by WHO and the FDA(0.80-1.25), demonstrating the bioequivalence of multisource T1 respect to the reference.